Down-regulation of hippocampal genes regulating dopaminergic, GABAergic and glutamatergic function following combined neonatal phencyclidine and post-weaning social isolation of rats as a neurodevelopmental model for schizophrenia - Gaskin, Philip L.R.; Toledo-Rodriguez, Maria; Alexander, Stephen P.H.; Fone, Kevin C.F. (Cambridge University Press, 2016)
Background: Dysfunction of dopaminergic, GABAergic and glutamatergic function underlies many core symptoms of schizophrenia. Combined neonatal injection of the N-methyl-D-aspartate (NMDA) receptor antagonist, phencyclidine (PCP) and post-weaning social isolation of rats produces a behavioral syndrome with translational relevance to several core symptoms of schizophrenia. This study uses DNA microarray to characterise alterations in hippocampal neurotransmitter-related gene expression and examines the ability of the sodium channel blocker, lamotrigine, to reverse behavioral changes in this model.